Tunable mid-infrared single-mode quantum cascade lasers - Shi, Hao (Nanyang Technological University, 2022)
Since the concept of quantum cascade laser (QCL) first proposed in 1997, the technology of QCL has grown rapidly and QCLs have been applied in many aera such as gas sensing and optical communication. The property of unipolar and subbands transition makes quantum cascade laser (QCL) ideal both mid-infrared and terahertz sources with narrow linewidth, high output power and tunable emission wavelength. The common solutions to realize single-mode tunable QCL are distributed feedback QCL (DFB-QCL) and external cavity QCL (EC-QCL). However, both of them suffer from some undesired drawbacks like complex fabrication, limited tuning range, and reduced robustness caused by vibration sensitive. In this dissertation, we designed and characterized a new QCL named slot waveguide QCL, which shows satisfying tunable single-mode performance.